Bachelor of Arts in Communication Students Asked: “What is my Contextual Communication Competence Level?” - Denzelle G. Gerardino; Allan Mark A. Fernandez; Joseph Quinto (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
In general, students need to be able to interact and communicate with one another from all walks of life, whether they are in personal or professional settings. Therefore, it is essential to examine students’ communication skills to ascertain whether they have adequate competence or not. In this regard, this research endeavored to determine the contextual communication competence of 266 Bachelor of Arts in Communication (BA Comm) students in one prime state university in Cordillera Administrative Region, Philippines. Through a quantitative-descriptive research design, one result revealed that BA Comm students are able to use their understanding of successful and appropriate communication patterns in public, meeting, group, and dyad situations with an average level of contextual communication competence. On the same level, BA Comm majors are committed to the field because they have the necessary communication abilities to adapt and improve various communication tactics when conversing with friends, acquaintances, and strangers. Lastly, compared to female BA Comm students, male students are more self-assured and open to communicating in various communication contexts, such as in public, meeting, group, or dyad contexts, as well as with strangers, friends, and acquaintances. Further, BA Comm students see a growth in their level of contextual communication competence as they move through their year levels because of their communication classes and social involvement. Recommendations are also included for future research directions.